ANALISIS PEMILIHAN JASA FORWARDER DENGAN MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) DI PT. XYZ - Ambar Wulan; Bambang Hendrawan (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2018)
Choosing a good and quality forwarder is something that cannot be considered easy. Errors in choosing a forwarding service will hinder the operational processes of a company, especially if the company is an international scale such as PT. XYZ. This study aims to choose the best forwarder services for the company. Criteria set by PT. XYZ in choosing forwarder services, namely Cost, Quality, Delivery, and Responsiveness. In this research forwarders who offer themselves or take part in bidding to work with PT. XYZ has only 4, namely forwarder A, forwarder B, forwarder C, and forwarder D. In this study the author uses the Analytical Hierarchy Process (AHP) method to determine which forwarder fits the company's criteria. The most important criteria for PT. XYZ is a Cost with the highest weight of 0.4841, Quality criteria with 0.2310, Delivery criteria with 0.1676 and Responsiveness criteria with 0.1171. then followed by forwarder A with the highest weight of 0.535, then forwarder B with 0.202, forwarder C with 0.145, and forwarder D with 0.119.